ChemInform Abstract: Efficient Synthesis of Eight‐Membered Nitrogen Heterocycles from O‐Propargylic Oximes by Rhodium‐Catalyzed Cascade Reactions. Issue 7 (29th January 2015) - Nakamura, Itaru; Sato, Yoshinori; Takeda, Keisuke; Terada, Masahiro
Abstract A series of azocine‐1‐oxides (II) is prepared by a Rh‐catalyzed 2, 3‐rearrangement/heterocyclization reaction sequence of corresponding O‐propargylic oximes (I).